2023
DOI: 10.1177/20552173221144229
|View full text |Cite
|
Sign up to set email alerts
|

Impact of treatment with dimethyl fumarate on sleep quality in patients with relapsing-remitting multiple sclerosis: A multicentre Italian wearable tracker study

Abstract: Background Sleep disorders are common in patients with multiple sclerosis and have a bidirectional interplay with fatigue and depression. Objective To evaluate the effect of treatment with oral dimethyl fumarate on the quality of sleep in relapsing-remitting multiple sclerosis. Methods This was a multicentre observational study with 223 relapsing-remitting multiple sclerosis subjects starting treatment with dimethyl fumarate ( n=177) or beta interferon ( n=46). All patients underwent subjective (Pittsburgh Sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…IFN-β and glatiramer acetate were found to prolong sleep-onset latency and cause frequent awakenings at night with poor sleep efficiency and daily somnolence [28,29]. On the contrary, natalizumab was shown to have a positive effect upon fatigue and daytime sleepiness [29] and dimethyl fumarate to ameliorate sleep problems [30]. Our findings demonstrated only slightly higher (on the edge of significance) EDSS score in the subgroup with sleep problems, and distribution of DMT did not differ between the subgroups.…”
Section: Discussioncontrasting
confidence: 58%
“…IFN-β and glatiramer acetate were found to prolong sleep-onset latency and cause frequent awakenings at night with poor sleep efficiency and daily somnolence [28,29]. On the contrary, natalizumab was shown to have a positive effect upon fatigue and daytime sleepiness [29] and dimethyl fumarate to ameliorate sleep problems [30]. Our findings demonstrated only slightly higher (on the edge of significance) EDSS score in the subgroup with sleep problems, and distribution of DMT did not differ between the subgroups.…”
Section: Discussioncontrasting
confidence: 58%
“…As we mentioned above, most of our study group used DMF as a current MS therapy. Comi et al obtained results that PwMS on DMF therapy had better sleep quality [31]. This study's main findings demonstrate that the primary risk factors for developing sleep disorders in individuals with MS were female gender, bladder disorders, and anxiety disorders.…”
Section: Discussionsupporting
confidence: 48%
“…As compared to Pokryszko-Dragan's study, their cohort of PwMS had a higher rate of insomnia of 49%, a higher EDSS score of 3.2, only 32% of PwMS were treated on interferon (IFN) or glatiramer acetate (GA), and as many as 66% of PwMS did not used DMT [30]. In our study, PwMS showed mild disability with a mean EDSS score of 2.4; what is more, almost all participants received DMT, mainly dimethyl fumarate (DMF), which does not lead to sleep disturbances like IFN or GA [31]. Perhaps due to this, they experienced better sleep quality.…”
Section: Discussionmentioning
confidence: 60%
“…The study explored fatigue as a secondary end point using the FSS. Despite the subjective self-reported improvement in fatigue due to significant positive effect on sleep quality, the study failed to demonstrate significant changes in fatigue, mobility or quality of life over the study duration [17].…”
Section: Ms Therapiesmentioning
confidence: 77%